Moral Life - "Pojman, Louis P." (New York, 2007)
Featuring new selections chosen by coeditor Lewis Vaughn, the third edition of Louis P. Pojman's The Moral Life: An Introductory Reader in Ethics and Literature brings together an extensive and varied collection of ninety-one classical and contemporary readings on ethical theory and practice. Integrating literature with philosophy in an innovative way, the book uses literary works to enliven and make concrete the ethical theory or applied issues addressed in each chapter. Literary works by Camus, Hawthorne, Hugo, Huxley, Ibsen, Le Guin, Melville, Orwell, Styron, Tolstoy, and many others lead students into such philosophical concepts and issues as relativism; utilitarianism; virtue ethics; the meaning of life; freedom and autonomy; sex, love, and marriage; animal rights; and terrorism. Once introduced, these topics are developed further through readings by philosophers including Plato, Aristotle, Kant, Nozick, Singer, and Sartre. This unique anthology emphasizes the personal dimension of ethics, which is often ignored or minimized in ethics texts. It also incorporates chapter introductions, study questions, suggestions for further reading, and biographical sketches of the writers. The third edition brings the collection up-to-date, adding selections by Jane English, William Frankena, Don Marquis, John Stuart Mill, Mary Midgley, Thomas Nagel, Judith Jarvis Thomson, and J.O. Urmson. It also features a new chapter on euthanasia with essays by Dan W. Brock, J. Gay-Williams, and James Rachels. Ideal for introductory ethics courses, The Moral Life, Third Edition, also provides an engaging gateway into personal and social ethics for general readers.
Keywords: Ethics